(3GdJMaI GdTGgjI (B( (3aj GdgjFI GdLSeGfjI (B)s - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s
(3ChdgG (B:s
(3NjQ GdeHGOF eGRjf HGdMeO CeG HYO , aEf eMehO Hf eSYhO jbhd (B: (3dhdG Cf GdSGOI ShZJ ddCUGZQ GdCfHSGW Edi GdCcGHQ QCjJ Gf CJMa ENJQJ efg Yde GdgjFI s
(3BNQgG (B:s
(3hjbSe gPG GdYOO Ydi YOO eKGd eG ajgG Ef cGf CUZQ efgG , aeG HdZ Ch NQL jchf YOO CeKGd eG ajg ef ecYH Gdejd hGdMeO ddg agPG eG SeMJ Hg bQjMJi LYdJg NOeI deYehQ NRGfI Gdehdi GdeYXe s
(3HgG fXGe GdJYbjHIs
(3HgG CTcGds
(3fSNI KGfjIs
(3jJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX HChdgG hba eDQN SfI (B1192 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B187 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B20 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B407s
Keywords: (3Gdadcs